(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
This work aims to find the differential scattering cross-section for X-ray scattered by aluminum target with angles in intervals in accordance to both polarization cases ( completely – partly). We found that the minimum and maximum values of lies in the range . In addition, the relative scattered intensity and polarization degree have been presented as a function of scattered angles and the extreme values are found for each curve.